Numerical simulation of temperature field during electron beam cladding for NbSi2 on the surface of Inconel617. (28th March 2018) - Liu, Hailang; Qi, Zhengwei; Wang, Bo; Zhang, Guopei; Wang, Xiaoyu; Wang, Dezhi
Abstract: Ansys was used to simulate the electron beam cladding temperature field of Inconel617 alloy with NbSi2 sprayed on the surface under the Gaussian heat source model, and the cladding experiment was carried out. By studying the influence of different process parameters on temperature field, it is found that when the electron beam = 19 mA, scanning speed = 8 mm s −1 and beam spot radius = 3 mm, the cladding effect is the best, and the molten pool is ellipsoidal. The temperature field is stable in the 1 s ∼ 4 s period, and the maximum temperature is 2769 K; the temperature of the sampling point on the X and Z paths increases rapidly with time, and then cools rapidly after rapid heating; The cladding experiment was carried out under the optimum parameters, it is found that the cladding layer is compact and the substrate is well bonded, thus verifying the accuracy of the simulation.